Super refractory status epilepticus in a parturient with preeclampsia undergoing cesarean delivery under spinal anesthesia (Indian Journal of Case Reports, 2022)
Super refractory status epilepticus (SRSE) is a rare but serious neurological emergency. This case report aims to highlight the challenges faced during the diagnosis and management of SRSE in a 36-year-old preeclamptic patient taken for cesarean delivery under spinal anesthesia. The patient developed a seizure episode minutes after administration of intrathecal bupivacaine, necessitating administration of general anesthesia. Postoperatively, SRSE developed which did not respond to multiple anti-epileptics and thiopentone sodium infusion. Although the clinical picture and magnetic resonance imaging findings supported the diagnosis of posterior reversible encephalopathy syndrome, the role of intrathecal bupivacaine in causing SRSE could not be ruled out due to the temporal association of events. The patient had a prolonged and complicated hospital stay and despite a multimodal approach to the treatment, suffered neurological sequelae.